SUMBER DAYA ALAM DAN POTENSI PARIWISATA RUMAH ADAT MABUR SEBAGAI IDENTITAS LIMA SUKU DI DESA TRIBUR - Nampi Irayani Blorton; Naomi Karpada; Norciana Well; Petrus Mau Tellu Dony (Adiba Aisha Amira, 2026)
Rumah Adat Mabur is one of the most significant cultural tourism assets in Tribur Village, possessing strong historical, architectural, and symbolic values for the local community. This study aims to analyze the tourism potential of Rumah Adat Mabur as a leading cultural attraction and to identify the challenges that hinder the development of the tourism sector in the village. A qualitative descriptive approach was employed through field observation, interviews with traditional leaders and residents, and documentation review. This method was used to capture the actual condition, community perceptions, and opportunities for cultural tourism development. The findings indicate that Rumah Adat Mabur holds strong cultural uniqueness, including its traditional architectural design, ancestral values, and its deep connection to community rituals and customs. These attributes make it a promising cultural tourism destination for both local and international visitors. However, the development of this potential remains limited due to inadequate infrastructure, lack of supporting facilities, minimal promotional efforts, and limited community skills in tourism management. Despite these challenges, support from local government, community training, and digital-based promotion strategies present significant opportunities to develop Rumah Adat Mabur as a cultural tourism icon of Tribur Village. The study concludes that Rumah Adat Mabur has strong potential to enhance the local economy and strengthen cultural identity if managed through a community-based tourism model. Planned, collaborative, and sustainable efforts are required to transform this cultural site into a driving force for tourism development in Tribur Village.